Clinical encounters about obesity: Systematic review of patients' perspectives. Issue 1 (2nd December 2019) - Ananthakumar, Thanusha; Jones, Nicholas R.; Hinton, Lisa; Aveyard, Paul
Summary: Guidelines recommend clinicians intervene on obesity but it is unclear how people with overweight react. In this systematic review, we searched 20 online databases for qualitative studies interviewing people with overweight or obesity who had consulted a primary care clinician. Framework synthesis was used to analyse 21 studies to produce a new theoretical understanding. Consultations in which patients discussed their weight were more infrequent than patients would have liked, which some perceived was because they were unworthy of medical time; others that it indicated doctors feel being overweight is not a serious risk. Patients reported that doctors offered banal advice assuming that the patient ate unhealthily or was not trying to address their weight. Patients reported doctors assumed that their symptoms were due to overweight without a proper history or examination, creating concern that serious illness may be missed. Patients responded positively to offers of support for weight loss and active monitoring of weight. Patients with overweight internalize weight stigma sensitizing them to clues that clinicians are judging them negatively, even if weight is not discussed. Patients' negative experiences in consultations relate to perceived snap judgements and flippant advice and negative experiences appear more salient than positive ones.